Respuesta :
♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️
[tex] - 8 \frac{3}{8} + 6 \frac{1}{4} = \\ [/tex]
[tex] \frac{ - 64 + 3}{8} + \frac{24 + 1}{4} = \\ [/tex]
[tex] \frac{ - 61}{8} + \frac{25}{4} = \\ [/tex]
[tex] \frac{ - 61}{8} + \frac{25 \times 2}{4 \times 2} = \\ [/tex]
[tex] \frac{ - 61}{8} + \frac{50}{8} = \\ [/tex]
[tex] \frac{ - 61 + 50}{8} = \\ [/tex]
[tex] \frac{ - 11 - 50 + 50}{8} = \\ [/tex]
[tex] \frac{ - 11}{8} = - \frac{11}{8} = - 1 \frac{3}{8} \\ [/tex]
♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️
Answer:
Step-by-step explanation:
8 = 2 * 2 * 2
4 = 2* 2
Least common denominator = 2 * 2 *2 = 8
[tex]-8\frac{3}{8}=-\frac{67}{8} \\\\6\frac{1}{4} = \frac{25}{4}\\[/tex]
[tex]-8\frac{3}{8}+6\frac{1}{4}=-\frac{67}{8}+\frac{25}{4}\\\\=-\frac{67}{8}+\frac{25*2}{4*2}\\\\=-\frac{67}{8}+\frac{50}{8}\\\\=\frac{-67+50}{8}\\\\=\frac{-17}{8}\\\\=-2\frac{1}{8}[/tex]